PENGARUH PEMBELAJARAN DIFERENSIASI BERBANTUAN WEBSITE GENIALLY TERHADAP HASIL BELAJAR SISWA KELAS IV SEKOLAH DASAR - Nurjana; Marhamah; Kuswidyanarko, Arief (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Mathematics is a tool for someone to think critically and help solve a problem. In learning mathematics using the lecture method is less effective because with this method the student's learning outcomes have not reached the maximum value. Based on this, the problem in this study is that teachers still use the lecture method so that students pay less attention to the teacher when delivering the material, the impact of which is that student learning outcomes are not optimal. The purpose of this study was to determine whether or not there was an effect of differentiation learning assisted by the Genially website on the learning outcomes of grade IV Elementary School students. The research method used was quantitative experiment. The results of the study showed that from the results of the tests that had been carried out, the average value obtained in the experimental class was 83.24 and the average value obtained in the control class was 60.16. And based on the data analysis that had been carried out using the hypothesis test, it was found that the sig value (2-tailed) of the post-test results of 0.000 was smaller than the significance level value of 0.05, so the Ho hypothesis was rejected and Ha was accepted, which means that there was an effect of differentiation learning assisted by the Genially website on student learning outcomes.Mathematics is a tool for someone to think critically and help solve a problem. In learning mathematics using the lecture method is less effective because with this method the student's learning outcomes have not reached the maximum value. Based on this, the problem in this study is that teachers still use the lecture method so that students pay less attention to the teacher when delivering the material, the impact of which is that student learning outcomes are not optimal. The purpose of this study was to determine whether or not there was an effect of differentiation learning assisted by the Genially website on the learning outcomes of grade IV Elementary School students. The research method used was quantitative experiment. The results of the study showed that from the results of the tests that had been carried out, the average value obtained in the experimental class was 83.24 and the average value obtained in the control class was 60.16. And based on the data analysis that had been carried out using the hypothesis test, it was found that the sig value (2-tailed) of the post-test results of 0.000 was smaller than the significance level value of 0.05, so the Ho hypothesis was rejected and Ha was accepted, which means that there was an effect of differentiation learning assisted by the Genially website on student learning outcomes.